Locus Coeruleus Norepinephrine in Learned Behavior: Anatomical Modularity and Spatiotemporal Integration in Targets - Breton-Provencher, Vincent; Drummond, Gabrielle T.; Sur, Mriganka (Frontiers in Neural Circuits, 2021)
The locus coeruleus (LC), a small brainstem nucleus, is the primary source of the neuromodulator norepinephrine (NE) in the brain. The LC receives input from widespread brain regions, and projects throughout the forebrain, brainstem, cerebellum, and spinal cord. LC neurons release NE tonically to control arousal, but also transiently in the context of a variety of sensory-motor and behavioral functions. Despite its brain-wide effects, much about the role of LC-NE in behavior and the circuits controlling LC activity is unknown. New evidence suggests that the modular input-output organization of the LC could enable phasic, task-specific modulation of distinct brain regions and behaviors. Future work must further assess whether this spatial modularity coincides with functional differences in LC-NE subpopulations acting at specific times, and how such spatiotemporal specificity might influence behavior. Here, we summarize the state of the field and present new ideas on the role of LC-NE in learned behaviors.